Endothelium-dependent desensitization to angiotensin II in rabbit aorta: the mechanisms involved - Jerez, Susana Josefina (2001)
The aim of this study was to characterize the role of the endothelium in angiotensin II-desensitization and its mechanisms of action. Rabbit aortic rings were exposed to increasing doses of angiotensin II (Ang II, 10–9 to 2.5 × 10–6) to generate two cumulative dose-response curves (CDRC I and II). A 50-min interval separated CDRC I and II. Desensitization was observed at all doses in unrubbed aortic tissue and at lower doses in rubbed aortic tissue. Tachyphylaxis was greater in arteries with endothelium. Treatment of intact rings with L-NG-nitroarginine methyl ester (L-NAME, 10–4 M) did not prevent this phenomenon. However, indomethacin (10–5 M) and miconazol (10–6 M) attenuated Ang II-desensitization. Treatment of unrubbed rings with nifedipine (10–6 M) and cromakalim (10–6 M) inhibited the effect of indomethacin. To confirm the involvement of K+ channels, unrubbed and rubbed aortic rings were treated with the KCa 2+ blockers apamin (10–7 M), tetraethylammonium (TEA, 10–3 M), and iberiotoxin (10–8 M), and the KATP blocker glibenclamide (10–5 M). In both arteries apamin, TEA, and glibenclamide abolished the tachyphylaxis without changes in the maximal response. Iberiotoxin diminished Ang II-desensitization in rubbed but not unrubbed arteries. Results from this study suggest that Ang II-desensitization involves endothelium-dependent and -independent mechanisms. Endothelium-dependent desensitization could be mediated by a cyclooxygenase-cytochrome P450 product, which could act by increasing KCa 2+ channel activity.